Effects of β- and κ-casein, and β-lactoglobulin single and composite genotypes on milk composition and milk coagulation properties of Italian Holsteins assessed by FT-MIR. Issue 1 (1st January 2021) - Cendron, Filippo; Franzoi, Marco; Penasa, Mauro; De Marchi, Massimo; Cassandro, Martino
Abstract: The present study aimed to investigate the effect of β- and κ- casein, and β-lactoglobulin genotypes on milk composition and milk coagulation properties predicted using Fourier-transform mid-infrared spectroscopy (FT-MIR). The final dataset provided 74, 721 observations from 5316 Holstein–Friesian cows reared in 122 herds in the Veneto region. Individual cow milk composition was obtained from Dairy Herd Improvement (DHI) testing between the years 2012 and 2021. Genotypes were analysed through customised bovine genotyping chip. The effect of both separate and combined milk protein genotype on major milk components, SCS, urea, and predicted milk coagulation properties, were investigated applying a linear mixed model. β-lactoglobulin BB resulted in the higher fat content, whereas protein and casein content was mostly enhanced by the k-casein BB haplotype. The urea content was significantly lower in β-lactoglobulin AA and k-casein EE genotypes and SCS was significantly lower in β-casein A1A1, β-lactoglobulin AA, and k-casein BB genotypes. Milk coagulation properties performance was significantly improved by β-casein A1A1, β-LG BB and k-casein BB, both as single variants and as composite genotype. The effect of genotypes on milk composition and milk coagulation properties showed five and four principal hierarchical clusters, respectively. Clustering highlighted unexpected relationships among genotypes in terms of final milk quality, suggesting it could be possible to select favourable genotypes maintaining sufficient diversity. HIGHLIGHTS: Milk protein variants have an impact on milk technological properties, but phenotype collection is laborious and expensive. Data collected using mid-infra-red spectroscopy can be used to estimate milk coagulation properties and perform population studies. Milk protein variants revealed unexpected relationships with milk composition and technological traits.